Dialogue, knowledge work and tabletops: Lessons from preservice teacher education - Ioannou, Andri; Zenios, Maria; Stylianou, Agni (My University, 2014)
This pilot study is concerned with the exploration of tabletops in preservice teacher education, through the lens of sociocultural theories. An educational tabletop application designed to facilitate dialog and collaborative decision making, so called IdeasMapping, was enacted in the context of proposing a solution plan for a case study classroom problem. Students' responses to a questionnaire showed that they positively endorsed the technology for this type of collaborative activity. Moreover, analysis of video recordings of groups' discussions and interactions showed that the technology enhanced students' communication as they took turns in sharing their ideas, and provided structure and organization of these ideas linked to possible solutions on the problems embedded in the case.
Keywords: Case based learning; Collaborative decision making; Collaborative learning; Educational technology; Interactive tables; Preservice teacher education; Surface computing; Tabletops; Technology integration